Analisa Produktivitas Mesin Pemarut dan Pemeras Ubi Kayu - Jatmiko Edi Siswanto (Universitas Batanghari, 2018)
The process of making tapioca flour traditionally consists of three stages performed separately. The three stages of tapioca flour production can also be done mechanically, ie with the help of equipment, both for the process of dissolving and the process of extortion and filtering. Existing mechanical means, using two separate tools in which one device is used for the dissolution process, while the other is used for extortion and filtering. 5 tests were performed with the scales specified in the test ie 2 kg, 4 kg, 6 kg, 8 kg, and 10 kg. The average engine capacity of 12 Kg / Hr and the capacity of cassava hardener is 11 Kg / hour. The average efficiency of flour testing was 20.54% and the average efficiency of cassava dregs was 37.8%.Key words: Productivity, Capacity, Efficiency